4CPS-161 Pharmacist interventions in a hospital at home unit. (24th March 2020) - Brito, A; Simoes, A; Alcobia, A
Abstract : Background and importance: Hospital at home (HaH) units provide hospital level care at home to patients who would otherwise remain hospitalised. A HaH unit is hospital based with a multidisciplinary team in which the pharmacist role is essential to provide pharmaceutical care in potential medication related problems. 1 Our HaH unit was started in 2015 and 1340 patients were admitted up to August 2019. Aim and objectives: To analyse pharmacist interventions (PIs) in HaH admitted patients. Material and methods: This was a retrospective study conducted between December 2018 and August 2019. All patients admitted to the HaH unit were included, except those <65 years of age or with <5 drugs prescribed. PIs made by email and by electronic notification were recorded. Telephone PIs were excluded. PIs were classified by intervention type (medication review, pharmacokinetics monitoring, prescription validation, information and therapeutic reconciliation), reason for intervention and therapeutic recommendation. Results: During the study period there were a total of 80 PIs in 53 patients from a total of 425 patients admitted to the HaH unit. Most patients (63.5%) had more than 10 drug prescriptions, and mean age was 74.7 years. The major PI were related to pharmacokinetic monitoring (45.0%), medication review (28.8%) and prescription validation (23.8%). The principal pharmaceutical recommendations were related to dose adjustment, low therapeutic index (34.6%), blood analysis for monitoring (23.5%) and alterations in prescribed drugs (16.0%). Thirteen cases of severe interactions were detected, of which 69.2% led to drug alteration and 30.8% to de-prescription. The acceptance rate of the pharmacist recommendations was 96.3%. Conclusion and relevance: PIs were mainly in polymedicated patients, reinforcing the need for pharmaceutical care in these high risk patients. Although the study population was small, compared with the total number of patients admitted to the HaH, the PIs showed a high impact, reducing potential harm to patients (antibiotics with low therapeutic index, detection of severe or moderate interactions). The high acceptance rate of the interventions by physicians revealed their importance and significance. Participation of a pharmacist in the HaH team contributes to improve patient safety and avoids drug related problems. References and/or acknowledgements: 1. Satti AE, et al. Impact of clinical pharmacist interventions in the medical ward—a study at Alkhor Hospital. Am J of PharmTech Res 2014 No conflict of interest.